THRIVE 2.0: A randomized-controlled trial of an obesity prevention intervention designed for infants in pediatric primary care - Tiffany M. Rybak; Sarah E. Francis; Constance A. Mara; Cynthia Zion; Avani C. Modi; Lori E. Crosby; Rachel B. Herbst; Brea A. Lauer; Bridget N. Murphy; Kasey R. Harry; Devanshi J. Patel; Mary Carol Burkhardt (Contemporary Clinical Trials Communications)
Background: Unprecedented rates of overweight and obesity are seen in childhood with evidence suggesting that infancy may be a critical period for the development of this elevated-weight trajectory. The impact of rapid growth in infancy on later obesity may differ by social stratification factors such as race/ethnicity and family income and be mediated by infant feeding and sleeping practices. This paper outlines the protocol for the Teaching Healthy Responsive Parenting during Infancy to promote Vital growth and rEgulation (THRIVE 2.0) intervention. Methods/design: This Phase 2b pilot randomized controlled trial will determine the feasibility, acceptability, satisfaction, and preliminary efficacy of the THRIVE 2.0 intervention compared with primary care treatment as usual (control). Caregiver-infant dyads will be recruited in pediatric primary care at their newborn visit and randomly assigned to THRIVE 2.0 (obesity prevention) or Control (usual pediatric care). Feasibility, acceptability, satisfaction, infant growth, feeding, and sleep will be assessed throughout the study period. Intervention will take place at regularly scheduled well-child visits at ages 1, 2, 4, and 6 months. Efficacy measures will be assessed at baseline, and 9 and 12 months of age. THRIVE is hypothesized to demonstrate efficacy for primary (e.g., conditional weight gain scores calculated from weight-for-length z-scores) and secondary outcomes (e.g., awareness of infant cues, use of alternative soothing strategies when it is not time for a feeding, and good infant sleep hygiene). Discussion: This paper outlines the planned procedures for the THRIVE 2.0 Phase 2b randomized controlled trial. Trial registration: Clinicaltrials.gov Identifier: NCT06028113 (October 10, 2023)